SHEET-LIKE STRUCTURE AND SHEET-LIKE STRUCTURE LAMINATE, STRUCTURED MEMBRANE AND PARTICLE COMPRISING THE SHEET-LIKE STRUCTURE AND SHEET-LIKE STRUCTURE LAMINATE, METHOD FOR PRODUCING THEM, AND SENSOR USING THE STRUCTURED MEMBRANE AND PARTICLE

A sheet-like structure of nickel-manganese composites in gas sensors addresses the lack of sensitivity in existing technologies, achieving improved detection of harmful gases through controlled morphology and resistance changes.

JP7609429B2Active Publication Date: 2025-01-07NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021143481
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-02
Publication Date
2025-01-07
Estimated Expiration
2041-09-02

AI Technical Summary

Technical Problem

Existing gas sensors lack development of nickel-containing substances, manganese-containing substances, or composites of these substances, limiting their sensitivity and selectivity for detecting harmful gases such as acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide.

Method used

A sheet-like structure composed of a composite of nickel-containing and manganese-containing substances, with controlled morphology and molar ratios, is used to create a sensor that exhibits a change in resistance value in response to these gases, allowing for improved detection.

Benefits of technology

The sensor demonstrates enhanced sensitivity and selectivity for detecting harmful gases, with resistance changes ranging from 1.0 to 6.2 for 5 ppm concentrations and up to 200 ppb for acetone, outperforming conventional sensors in selectivity and sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609429000005
    Figure 0007609429000005
  • Figure 0007609429000006
    Figure 0007609429000006
  • Figure 0007609429000007
    Figure 0007609429000007
Patent Text Reader

Abstract

To provide a sheet-like structure composed of a composite of a nickel-containing material and a manganese-containing material having nanostructures that are useful as gas sensors for detecting combustible and reducing gases such as acetone, isoprene, toluene, ammonia, and hydrogen, as well as oxidizing and combustion-supporting gases such as nitrogen dioxide, a structural membrane composed of the sheet-like structure and particles, a production method thereof, and a sensor using these sheet-like structure and particles.SOLUTION: The sheet-like structure includes any of the composites of nickel-containing and manganese-containing materials and has a sheet-like shape. The sheet-like structure is a structural film and particles that are formed by bonding in a state of crystal growth.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sheet-like structure and a sheet-like structure laminate, a structured film and particles each made of the sheet-like structure and the sheet-like structure laminate, and a method for producing the same, and a sensor using the structured film or particles. [Background technology]

[0002] In gas sensors, molecular sensors, catalysts, batteries, etc., the composition, crystallinity, microstructure, crystal plane, surface area, etc. of materials have a large effect on their characteristics. Therefore, there is a demand for controlling the composition, crystallinity, microstructure, crystal plane, surface area, etc. of materials to improve their characteristics.

[0003] Patent Document 1 describes a metal oxide semiconductor MEMS gas sensor that detects low concentration gas. In Patent Document 1, the metal oxide semiconductor of the MEMS gas sensor is preferably a thick film, and between a film thickness of 40 μm and 4 μm, the toluene sensitivity was much higher at 40 μm. The film thickness is preferably 10 μm to 100 μm, and more preferably 20 μm to 60 μm. In Patent Document 1, the metal oxide semiconductor is made of Pd-loaded SnO2 nanoparticles. The nanoparticles have an average secondary particle diameter of less than 1 μm, preferably 100 nm or less. Particularly preferably, monodisperse SnO2 particles loaded with Pd and having an average particle diameter of less than 100 nm are described as the metal oxide semiconductor.

[0004] However, although Patent Document 1 develops a gas sensor using Pd-loaded SnO2 nanoparticles, it does not report on nickel-containing substances, manganese-containing substances, or composites of nickel-containing substances and manganese-containing substances.

[0005] On the other hand, in Patent Document 2, some of the Sn atoms on the SnO2 surface are replaced with Zr atoms, or oxygen defects on the surface of SnO2 particles are replaced with oxygen bonded to Zr atoms. In this case, the concentration of Zr atoms in SnO2 relative to the total of Zr atoms and Sn atoms is set to 0.01 at% or more and 0.2 at% or less. This provides an SnO2-based gas sensor with increased sensitivity to hydrogen and CO.

[0006] Patent Document 2 provides a SnO2-based gas sensor that has increased sensitivity to hydrogen and CO by replacing some of the Sn atoms on the SnO2 surface with Zr atoms, or by replacing oxygen defects on the surface of SnO2 particles with oxygen bonded to Zr atoms. However, it does not report on nickel-containing substances, manganese-containing substances, or composites of nickel-containing substances and manganese-containing substances.

[0007] As can be seen from these patent documents, many of the existing gas sensors use SnO2, and there are few development examples relating to nickel-containing substances, manganese-containing substances, or composites of nickel-containing substances and manganese-containing substances. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2020-041833 A [Patent Document 2] JP 2018-31696 A [Non-patent literature]

[0009] [Non-Patent Document 1] https: / / www.figaro.co.jp / product / entry / tgs2602.html [Non-Patent Document 2] https: / / www.figaro.co.jp / product / docs / tgs2602_product%20information%28jp%29_rev04.pdf Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made in consideration of the above circumstances, and aims to provide a sheet-like structure and a laminate thereof consisting of a composite of a nickel-containing material and a manganese-containing material having a nanostructure, which are useful as a gas sensor for detecting flammable gases and reducing gases, such as acetone, isoprene, toluene, ammonia, and hydrogen, as well as oxidizing gases and combustion-supporting gases, such as nitrogen dioxide, and a structure film or particle formed from the sheet-like structure or the laminate thereof, methods for producing them, and a sensor using these structure films or particles. [Means for solving the problem]

[0011] According to the present invention, in order to achieve the above-mentioned object, there are provided a sheet-like structure having the following configuration, a structured film and particles made of the sheet-like structure, and methods for producing them, as well as a sensor using the structured film and particles.

[0012] First, the sheet-like structure of the present invention is characterized in that it contains a composite of a nickel-containing substance and a manganese-containing substance and has a sheet-like form. Secondly, the sheet-like structure laminate of the present invention is characterized in that the sheet-like structure of the first invention is laminated, and the number of laminated sheets is two or more. Thirdly, the structure film of the present invention is characterized in that it is formed by bonding the sheet-like structure of the first invention and / or the sheet-like structure laminate of the second invention in a crystal-grown state. Fourthly, in the structural film of the third invention, the molar ratio of manganese to nickel in the structural film is 0.17 or more and 0.83 or less, or the molar ratio of nickel to manganese is 0.17 or more and 0.83 or less. Fifth, in the structural film of the third or fourth invention, the sheet-like structure and / or the sheet-like structure laminate in the structural film are The longitudinal length L (nm) is in the range of 20 to 400 nm, The thickness T (nm) ranges from 5 to 30 nm. It is characterized in that the ratio R of the longitudinal length L (nm) to the thickness T (nm) (aspect ratio: L / T) is in the range of 3-40. Sixthly, the particle of the present invention is characterized in that it is constituted by bonding the sheet-like structure of the first invention and / or the sheet-like structure laminate of the second invention in a crystal-grown state. Seventh, the particles according to the sixth invention are characterized in that the molar ratio of manganese to nickel in the particles is 0.17 or more and 0.83 or less, or the molar ratio of nickel to manganese in the particles is 0.17 or more and 0.83 or less. Eighth, in the particle according to the sixth or seventh invention, the sheet-like structure and / or the sheet-like structure laminate in the particle are: The longitudinal length L (nm) is in the range of 100 to 1800 nm, The thickness T (nm) ranges from 10 to 100 nm. It is characterized in that the ratio R (aspect ratio: L / T) of the longitudinal length L (nm) to the thickness T (nm) is in the range of 5-34. Ninthly, the method for producing a structure film of the present invention is the method for producing a structure film of the third or fourth aspect, comprising the steps of: immersing a substrate in a solution containing at least nickel element to cause nucleation and crystal growth of the sheet-like structure made of a nickel-containing substance on a substrate surface; forming a structure film composed of the sheet-like structure and the sheet-like structure laminate made of the nickel-containing substance on the substrate; and The substrate is immersed in a solution containing at least elemental manganese, thereby causing nucleation and crystal growth of the sheet-like structure made of a manganese-containing material on the substrate surface, and forming a composite structure film composed of the sheet-like structure and the sheet-like structure laminate, which is made of a complex of the nickel-containing material and the manganese-containing material. Tenthly, the method for producing a structure film of the present invention is the method for producing a structure film of the third or fourth aspect, comprising the steps of: immersing a substrate in a solution containing at least elemental manganese to cause nucleation and crystal growth of the sheet-like structure made of a manganese-containing substance on a substrate surface; forming a structure film composed of the sheet-like structure and the sheet-like structure laminate made of the manganese-containing substance on the substrate; The method is characterized in that the substrate is immersed in a solution containing at least nickel element, thereby causing nucleation and crystal growth of the sheet-like structure made of a nickel-containing material on the substrate surface, and forming a composite structure film composed of the sheet-like structure and the sheet-like structure laminate, which is made of a composite of the manganese-containing material and the nickel-containing material. An eleventh aspect of the present invention is a method for producing particles according to any one of the sixth to eighth aspects of the present invention, comprising the steps of: maintaining a solution containing at least nickel element at a predetermined temperature for a predetermined time, and then allowing it to cool, thereby carrying out nucleation and crystal growth of the sheet-like structure made of a nickel-containing substance; forming particles composed of the sheet-like structure and the sheet-like structure laminate made of the nickel-containing substance; and then: The particles are kept in a solution containing at least elemental manganese at a predetermined temperature for a predetermined time, and then allowed to cool, thereby causing nucleation and crystal growth of the sheet-like structure made of a manganese-containing material, and forming composite particles composed of the sheet-like structure and the sheet-like structure laminate, which are made of a complex of the nickel-containing material and the manganese-containing material. Twelfthly, the method for producing particles of the present invention is any one of the methods for producing particles according to the sixth to eighth aspects, and further comprises the steps of: maintaining a solution containing at least manganese element at a predetermined temperature for a predetermined time, and then allowing it to cool, thereby carrying out nucleation and crystal growth of the sheet-like structure made of a manganese-containing substance; forming particles composed of the sheet-like structure and the sheet-like structure laminate made of the manganese-containing substance; and then: The particles are kept in a solution containing at least nickel element at a predetermined temperature for a predetermined time, and then allowed to cool, thereby causing nucleation and crystal growth of the sheet-like structure made of a nickel-containing material, and forming composite particles composed of the sheet-like structure and the sheet-like structure laminate, which are made of a complex of the manganese-containing material and the nickel-containing material. Thirteenth, the sensor of the present invention comprises a substrate; A pair of electrodes provided on the substrate; a structural film according to any one of claims 3 to 5 and / or particles according to any one of claims 6 to 8 formed on the electrode; The present invention is characterized by having the following. 14. The sensor of the 13th invention, wherein the sensor is a gas sensor and exhibits a resistance change of more than 1.0 and not more than 6.2 with respect to a reducing gas having a concentration of 5 ppm or an oxidizing gas having a concentration of 5 ppm. A fifteenth aspect of the present invention is the sensor according to the thirteenth aspect, characterized in that the sensor is a gas sensor which exhibits a resistance change of more than 1.0 and not more than 1.8 with respect to acetone at a concentration of 200 ppb. 16. The sensor according to the 13th aspect of the present invention is characterized in that the sensor is a gas sensor which has an acetone selectivity of a ratio greater than 1.0 and less than 5.1 when comparing the resistance change in response to acetone with the resistance change in response to isoprene, toluene, ammonia, hydrogen, or nitrogen dioxide. 17. The sensor according to the 13th aspect of the present invention, wherein the sensor is a gas sensor capable of detecting one or more of acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide gases at a concentration of 5 ppm. 18. The sensor according to the 13th aspect of the present invention, wherein the sensor is a gas sensor capable of detecting acetone gas at a concentration of 200 ppb. Effect of the Invention

[0013] The sheet-like structure and sheet-like structure laminate of the present invention have a sheet-like form containing a composite of a nickel-containing substance and a manganese-containing substance, and can be formed in an aqueous solution without using a pressure vessel or a high-temperature device. In addition, since the form in the microstructure is controlled, the properties can be improved compared to conventional particles having an irregular sheet form.

[0014] In addition, the structured film and particles of the present invention are composed of the sheet structure and sheet-like structure laminate of the present invention, and are formed by nucleation, crystal growth, and bonding. In particular, the structured film is formed by nucleation, crystal growth, and bonding on the surface of the substrate. It can be formed uniformly at the location in contact with the solution. Therefore, in addition to flat plates and films, composite materials can be formed with uneven substrates, meshes, nonwoven shapes, particles, tubes, the inside and outside of containers, three-dimensional members such as gears, etc. In addition, since it is a method of contacting with a solution, composite materials with uneven members of several nanometers and uneven members of several tens of meters can be formed, and can be suitably used as a material for sensors such as gas sensors, molecular sensors, and solution sensors.

[0015] In particular, when the sensor of the present invention is applied to a gas sensor, it can be used as a gas sensor for detecting a combustible gas, a reducing gas, an oxidizing gas such as nitrogen dioxide, or a combustion-supporting gas. Specifically, any of acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide gas can be detected. [Brief description of the drawings]

[0016] [Figure 1] This is a scanning electron microscope photograph of a composite structure film consisting of a composite of a nickel-containing material and a manganese-containing material (synthesis time of manganese-containing structure film: 10 minutes). [Diagram 2] 1 is a scanning electron microscope photograph showing the state of a sheet-like structure and a sheet-like structure laminate of a composite structure film made of a composite of a nickel-containing material and a manganese-containing material (synthesis time of manganese-containing structure film: 10 minutes). [Diagram 3]This is a scanning electron microscope photograph of a composite structure film consisting of a composite of a nickel-containing material and a manganese-containing material (synthesis time of manganese-containing structure film: 4 hours). [Figure 4] 1 is a scanning electron microscope photograph showing the state of a sheet-like structure and a sheet-like structure laminate of a composite structure film made of a composite of a nickel-containing material and a manganese-containing material (synthesis time of manganese-containing structure film: 4 hours). [Diagram 5] This is a scanning electron microscope photograph of a composite structure film consisting of a composite of a nickel-containing material and a manganese-containing material (synthesis time of manganese-containing structure film: 24 hours). [Figure 6] 1 is a scanning electron microscope photograph showing the state of a sheet-like structure and a sheet-like structure laminate of a composite structure film made of a composite of a nickel-containing material and a manganese-containing material (synthesis time of manganese-containing structure film: 24 hours). [Figure 7] This is a scanning electron microscope photograph of a composite particle consisting of a composite of a nickel-containing material and a manganese-containing material (immersion time in the manganese-containing solution: 10 minutes). [Figure 8] 1 is a scanning electron microscope photograph showing the state of a sheet-like structure and a sheet-like structure laminate of composite particles consisting of a composite of a nickel-containing material and a manganese-containing material (immersion time in a manganese-containing solution: 10 minutes). [Figure 9] 1 shows X-ray diffraction patterns of a structure film made of a nickel-containing material synthesized in Reference Example 1 and a composite structure film made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1. [Figure 10] Diffraction patterns of a structure film made of a nickel-containing material synthesized in Reference Example 1 and a composite structure film made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1 were evaluated by X-ray diffraction after heat treatment at 400°C for 5 hours in air. [Figure 11] 1 is a graph showing the composition of nanostructured particles made of a nickel-containing material synthesized in Reference Example 2 and composite structure particles made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 2, evaluated by X-ray photoelectron spectroscopy (XPS). [Figure 12] 1 is a graph showing the sensor sensitivity to various gases for a structure film made of a nickel-containing material synthesized in Reference Example 1 and a composite structure film made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1 (immersion time in a manganese-containing solution: 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours). [Figure 13] 1 is a graph showing the sensor sensitivity to a low concentration of 200 ppb of acetone at each sensor element temperature for a composite structure film made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1 (immersion time in a manganese-containing solution: 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, the present invention will be described in detail based on embodiments. The sheet-like structure of the present invention has a sheet-like form made of a composite of a nickel-containing material and a manganese-containing material. It may also have a laminated structure of a small sheet and a large sheet, and in the case of a sheet-like structure laminate having a laminated structure, the number of laminated sheets is 2 or more, and usually 2 to 3.

[0018] Examples of nickel-containing substances that can be used as raw materials for the sheet-like structure of the present invention and nickel-containing substances that can be synthesized include the following substances. Nickel oxide, Nickel hydroxide, Nickel(II) hydroxide, Nickel chloride hexahydrate (NiCl2·6H2O), Nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No. 38-0715), Nickel Nickel(II) fluoride, Nickel(II) fluoride tetrahydrate, Nickel(II) iodide, Hexaamminenickel(II) iodide, Nickel boride, Nickel silicide, Nickel(II) chloride, Nickel(II) chloride hexahydrate, Nickel(II) chloride hydrate, Nickel(II) chloride (dimethoxyethane adduct), Hexaamminenickel(II) chloride, Bis(triphenylphosphine)nickel(II) chloride, Methallylnickel chloride dimer, Nickel(II) nitrate hexahydrate, Nickel(II) nitrate solution , Nickel(II) acetate tetrahydrate, Nickel(II) hydroxyacetate, Nickel(II) sulfide, Nickel(II) sulfate hydrate, Nickel(II) sulfate hexahydrate, Nickel(II) ammonium sulfate hexahydrate, Nickel(II) amidosulfate tetrahydrate, Nickel(II) carbonate, Nickel(II) carbonate (basic) hydrate, Nickel(II) bromide, Nickel(II) bromide trihydrate, Nickel(II) bromide hydrate, Nickel(II) lactate tetrahydrate, Nickel(II) formate dihydrate, Nickel(II) citrate hydrate , Nickel(II) oxalate dihydrate, Nickel(II) sulfamate, Nickel sulfamate hydrate, Nickel(II) amidosulfate hydrate, Nickel(II) cyclohexanebutyrate, Nickel(II) 2-ethylhexanoate, Nickel(II) trifluoromethanesulfonate, Nickel(II) naphthenate, Nickel(II) acetylacetonate, Nickel(II) 2,4-pentanedionate, Nickel(II) cyanide tetrahydrate, Nickel(II) trifluoroacetate tetrahydrate, Nickel(II) tetrafluoroboronate Nickel(II) acid hexahydrate, basic nickel(II) carbonate, nickel(II) perchlorate hexahydrate, nickel(II) acetylacetonate hydrate, potassium hexafluoronickelate(IV), potassium tetracyanonickelate(II) hydrate, nickel tungsten oxide, nickel molybdenum oxide, nickel iron oxide, nickel chromite, nickel chromium, nickel telluride, lanthanum nickel, LiNiPO4, nickel dimethylglyoxime, nickel(II) phthalocyanine, nickel(II) acetylacetonate hydrate, nickel(II) trifluoroacetylacetonate dihydrate, nickel(II) 1,3-Bis(diphenylphosphine)propane chloride, nickel 2-methoxyethoxide, bis(triphenylphosphine)nickel(II) iodide, tetrabutylphosphonium bis(1,2-benzenedithiolato)nickel(III)ate, bis(tricyclohexylphosphine)nickel(II) chloride, bis(N,N'-di-t-butylacetamidoynato)nickel(II), bis(1,5-cyclooctadiene)nickel, bis(cyclopentadienyl)nickel, also known as nickelocene, bis(triphenylphosphine)dicarbonylnickel, bis(ethylcyclopentadienyl)nickel, bis(isopropylcyclopentadienyl)nickel, bis(pentamethylcyclopentadienyl)nickel, bis(tetramethylcyclopentadienyl)nickel, (ethylcyclopentadienyl)nickel, potassium tetracyanonickelate(II) monohydrate, dichloro[1,2-bis(diphenylphosphino)ethane]nickel(II), dichlorobis(triphenylphosphine)nickel(II), bis(2,2,6,6-tetramethyl-3,5-heptanedionato)nickel(II), bis(triphenylphosphine)nickel dicarbonyl, bis(dibutyldithiocarbamate)nickel(II), bis(triphenylphosphine)nickel(II) bromide, meso-tetraphenylporphinenickel(II), chlorobis(triphenylphosphine)nickel(II), dichlorobis(triphenylphosphine)nickel(II), trifluoroacetylacetonatenickel, dihydrate, 1,2-bis(diphenylphosphino)ethanenickel chloride, hexafluoroacetylacetonatenickel(II) hydrate, dichloro[bis(1,3-diphenylphosphino)propane]nickel(II), [1,3-bis(diphenylphosphino)propane]dichloronickel(II), bis(2,2,6,6-tetramethyl-3,5-heptanedionato)nickel(II), dichloro[1,1'-bis(diphenylphosphino)ferrocene]nickel(II),

[0019] Examples of the manganese-containing material to be used as the raw material for the sheet-like structure of the present invention and the manganese-containing material to be synthesized include the following materials. Manganese oxide, manganese(IV) oxide, manganese hydroxide, manganese, potassium permanganate, manganese(II) methoxide, manganese(II) fluoride, manganese(III) fluoride, manganese(II) iodide, manganese phosphide, manganese(II) sulfide, manganese aluminide, manganese(IV) telluride, manganese(II) selenide, barium manganate, potassium manganate, manganese(II) molybdate, manganese titanate, manganese(II) titanium oxide, manganese(II) tungsten oxide, manganese(II) acetate, manganese(III) acetate dihydrate, manganese acetate Manganese(II) tetrahydrate, meso-tetraphenylporphine manganese(III) acetate, manganese(II) chloride, manganese(II) chloride tetrahydrate, manganese(II) sulfate monohydrate, manganese(II) sulfate pentahydrate, manganese(II) sulfate tetrahydrate, manganese(II) nitrate, manganese(II) nitrate tetrahydrate, manganese(II) nitrate hexahydrate, manganese(II) carbonate, manganese(II) carbonate n-hydrate, manganese(II) formate, manganese(III) phosphate hydrate, manganese(II) phosphate monobasic tetrahydrate, manganese(II) hypophosphite monohydrate, manganese(II) bromide Manganese(II) bromide tetrahydrate, Manganese(II) oxalate dihydrate, Manganese naphthenate, Manganese(II) perchlorate hexahydrate, Manganese(II) benzoate tetrahydrate, Manganese(II) 2-ethylhexanoate, Manganese(II) gluconate dihydrate, Manganese(II) cyclohexanebutyrate, Bis(tetramethylcyclopentadienyl)manganese(II), Bis(pentamethylcyclopentadienyl)manganese(II), Manganese(III) 2,4-pentanedionate, Manganese(II) ethylenediamine-N,N,N',N'-tetraacetate disodium salt trihydrate, Manganese(III) acetylacetonate, Manganese carbonyl, Manganese(II) phthalocyanine, Bis(cyclopentadienyl)manganese Bis(isopropylcyclopentadienyl)manganese, bis(tetramethylcyclopentadienyl)manganese, bis(pentamethylcyclopentadienyl)manganese, (1S,2S)-(+)-[1,2-cyclohexanediamino-N,N'-bis(3,5-di-t-butylsalicylidene)]manganese(III) chloride, mangafodipyr trisodium, methylcyclopentadienylmanganese tricarbonyl, tris(2,2,6,6-tetramethyl-3,5-heptanedionato)manganese(III), pentacarbonylmanganese bromide, bis(ethylcyclopentadienyl)manganese, cyclopentadienylmanganese tricarbonyl, methylcyclopentadienylmanganese tricarbonyl Bromopentacarbonylmanganese(I), tris(2,2,6,6-tetramethyl-3,5-heptanedionato)manganese(III), bis(cyclopentadienyl)manganese(II), mancozeb ([C4H6MnN2S4] x Zinc y ),

[0020] The sheet-like structure and the sheet-like structure laminate of the present invention can take the form of a structured film or particles. The structured film is formed by immersing a substrate in a solution containing at least nickel or manganese element, treating the substrate under a predetermined condition, and then immersing the substrate in a solution containing at least manganese or nickel element, treating the substrate under a predetermined condition, so that a chemical reaction in the solution causes nucleation and crystal growth of a sheet-like structure made of a composite of a nickel-containing substance and a manganese-containing substance to proceed on the substrate surface, and the composite is bonded to form a structured film made of the sheet-like structure and the sheet-like structure laminate.

[0021] Specifically, a method for forming a composite structure film made of a composite of a nickel-containing material and a manganese-containing material on a substrate surface is, for example, to first add urea and nickel chloride hexahydrate to a mixed solution of distilled water and ethanol, and then dissolve the mixture by stirring at room temperature. The substrate is immersed in the solution and held at a predetermined temperature for a predetermined time, and then allowed to cool naturally to form a structure film made of a nickel-containing material on the substrate surface. In this case, the predetermined temperature is considered to be about 0 to 100°C, and the predetermined time is considered to be about 10 minutes to 24 hours.

[0022] Next, potassium permanganate (KMnO4) is added to distilled water, stirred at room temperature, and dissolved in the solution, and the substrate is immersed in the solution, held at a predetermined temperature for a predetermined time, and then allowed to cool naturally. This allows a composite structure film made of a composite of a nickel-containing material and a manganese-containing material to be formed on the substrate. In this case, the predetermined temperature is about 0 to 100°C, and the predetermined time is about 10 minutes to 24 hours.

[0023] Here, the molar ratio of manganese to nickel in the composite structure film made of a composite of a nickel-containing substance and a manganese-containing substance is in the range of 0.17 or more and 0.83 or less. The above-mentioned structural film can be formed at normal pressure (atmospheric pressure, 1 atm).

[0024] In addition, as a method for forming a composite structure film according to another embodiment of the present invention, for example, potassium permanganate (KMnO4) is added to distilled water, stirred at room temperature to dissolve the solution, and a substrate is immersed in the solution, which is then held at a predetermined temperature for a predetermined time and then allowed to cool naturally. This allows a composite structure film made of a composite of a nickel-containing material and a manganese-containing material to be formed on the substrate. In this case, the predetermined temperature is about 0 to 100°C, and the predetermined time is about 10 minutes to 24 hours.

[0025] Next, urea and nickel chloride hexahydrate are added to a mixed solution of distilled water and ethanol, and then the solution is stirred at room temperature to dissolve the urea and nickel chloride hexahydrate. The substrate is immersed in the solution and held at a predetermined temperature for a predetermined time, and then allowed to cool naturally to form a structural film made of a nickel-containing substance on the substrate surface. In this case, the predetermined temperature is about 0 to 100°C, and the predetermined time is about 10 minutes to 24 hours.

[0026] Here, the molar ratio of nickel to manganese in the composite structure film made of a composite of a manganese-containing substance and a nickel-containing substance ranges from 0.17 to 0.83. The formation of the above-mentioned structural film can also be carried out at normal pressure (atmospheric pressure, 1 atm).

[0027] The size range of the sheet-like structure in the structure film of the present invention is preferably considered to be a longitudinal direction L (nm) range of 20 to 400 nm, a thickness T (nm) range of 5 to 30 nm, and a ratio R (aspect ratio: L / T) of the longitudinal length L (nm) to the thickness T (nm) range of 3 to 40.

[0028] The structural film made of the composite of the nickel-containing material and the manganese-containing material in the above embodiment is formed by nucleation, crystal growth, and bonding on the surface of the base material, so that the structural film is closely attached and fixed to the substrate.

[0029] In addition, since the structural membrane can be formed in an aqueous solution without using a pressure vessel or high-temperature equipment, it is possible to form composite materials with plastic substrates, polymer films, paper, metals, glass, carbon materials, biomaterials, etc.

[0030] On the other hand, in the sintering method, which requires high-temperature heat treatment at several hundred degrees, it is difficult to form a structural film made of a nickel-containing substance, a manganese-containing substance, or a composite of a nickel-containing substance and a manganese-containing substance on plastic substrates, polymer films, paper, metals, glass, carbon materials, biomaterials, etc., which are prone to combustion and deterioration.

[0031] In addition, because the structured film can be formed uniformly in the area in contact with the solution, in addition to flat plates and films, it can also form composite materials with uneven substrates, meshes, nonwoven fabric shapes, particles, tubes, the inside and outside of containers, gears, and other three-dimensional components. In addition, because it is a method of contacting with the solution, it is possible to form composite materials with uneven components of several nanometers or tens of meters.

[0032] On the other hand, in the sintering method, which requires high-temperature heat treatment at several hundred degrees, it is necessary to apply a particle-containing paste, and it is difficult to form a structured film made of a composite of a nickel-containing substance and a manganese-containing substance on the surface of a three-dimensional member such as an uneven substrate, a mesh, a nonwoven fabric shape, particles, a tube, the inside and outside of a container, or a gear. In addition, it is necessary to uniformly apply a highly viscous particle-containing paste, and it is difficult to form a structured film made of a composite of a nickel-containing substance and a manganese-containing substance on a small uneven member of several micrometers or less. In addition, in the sintering method, which requires high-temperature heat treatment at several hundred degrees in a sintering furnace, the size of the sintering furnace is a limitation, and it is difficult to form a structured film made of a composite of a nickel-containing substance and a manganese-containing substance on a large equipment exceeding 1 meter.

[0033] The particles are formed by treating a solution containing at least nickel or manganese element under specified conditions, and then immersing the solution in a solution containing at least manganese or nickel element and treating the solution under specified conditions, thereby promoting nucleation and crystal growth of a sheet-like structure consisting of a composite of a nickel-containing material and a manganese-containing material through a chemical reaction in the solution, thereby bonding the sheet-like structure and forming particles consisting of the sheet-like structure and a sheet-like structure laminate.

[0034] A specific method for forming composite particles consisting of a composite of a nickel-containing substance and a manganese-containing substance is, for example, to add urea and nickel chloride hexahydrate to a mixed solution of distilled water and ethanol, dissolve them by stirring at room temperature, hold the mixture at a predetermined temperature for a predetermined time, and then naturally cool the mixture. The precipitated particles are taken out, washed with water, and naturally dried to obtain particles consisting of a nickel-containing substance. In this case, the predetermined temperature is about 0 to 100°C, and the predetermined time is about 10 minutes to 24 hours.

[0035] Next, potassium permanganate (KMnO4) is added to distilled water, and the solution is stirred and dissolved at room temperature. The particles made of the nickel-containing material are immersed in the solution, and after maintaining the solution at a predetermined temperature for a predetermined time, the solution is naturally cooled, and the precipitated particles are taken out, washed with water, and naturally dried. In this way, composite particles made of a composite of a nickel-containing material and a manganese-containing material can be obtained. In this case, the predetermined temperature is about 0 to 100°C, and the predetermined time is about 10 minutes to 24 hours.

[0036] Here, the molar ratio of manganese to nickel in the composite particles made of a composite of a nickel-containing substance and a manganese-containing substance is in the range of 0.17 or more and 0.83 or less. The particles can be formed at normal pressure (atmospheric pressure, 1 atm).

[0037] In addition, as a method for forming composite particles according to another embodiment of the present invention, for example, potassium permanganate (KMnO4) is added to distilled water, stirred at room temperature to dissolve, and then the mixture is kept at a predetermined temperature for a predetermined time, and then allowed to cool naturally. The precipitated particles are taken out, washed with water, and naturally dried to obtain particles made of a manganese-containing substance. In this case, the predetermined temperature is considered to be about 0 to 100°C, and the predetermined time is considered to be about 10 minutes to 24 hours.

[0038] Next, urea and nickel chloride hexahydrate are added to a mixed solution of distilled water and ethanol, and the solution is stirred at room temperature to dissolve the urea and nickel chloride hexahydrate. The particles made of the manganese-containing material are then immersed in the solution, and the solution is kept at a predetermined temperature for a predetermined time, and then allowed to cool naturally. The precipitated particles are taken out, washed with water, and naturally dried. This allows the production of composite particles made of a composite of a manganese-containing material and a nickel-containing material. The predetermined temperature in this case is about 0 to 100°C, and the predetermined time is about 10 minutes to 24 hours.

[0039] Here, the molar ratio of nickel to manganese in the composite particles made of a composite of a manganese-containing substance and a nickel-containing substance ranges from 0.17 to 0.83. The particles can also be formed at normal pressure (atmospheric pressure, 1 atm).

[0040] The size range of the sheet-like structure having a sheet-like morphology in the particle of the present invention is preferably considered to be a longitudinal direction L (nm) range of 100 to 1800 nm, a thickness T (nm) range of 10 to 100 nm, and a ratio R (aspect ratio: L / T) of the longitudinal length L (nm) to the thickness T (nm) range of 5 to 34.

[0041] In addition, including sheets with an unclear thickness (thickness less than 10 nm), it is preferable that the longitudinal length L (nm) range is 100 to 1800 nm, the thickness T (nm) range is 10 to 100 nm, and the ratio R (aspect ratio: L / T) of the longitudinal length L (nm) to the thickness T (nm) range is 5 to 180.

[0042] In the molding of the above-mentioned structural film or particle of the present invention, after the above-mentioned process, a heat treatment can be further performed in which the substrate on which the structural film has been formed or the particle is placed in an electric furnace, the temperature is raised from room temperature to about 100 to 1000°C in the atmosphere, the temperature is maintained while heating for about 10 minutes to 24 hours, and then the substrate or particle is naturally cooled.

[0043] The above-mentioned structure film and particles of the present invention can be suitably used as a sensor material. The sensor can be made into a sensor element by forming a structure film made of the above-mentioned nickel-containing substance, manganese-containing substance, or a composite of the nickel-containing substance and manganese-containing substance of the present invention on a base material such as a substrate having a metal electrode, or by forming particles as a particle film by a coating method or the like.

[0044] In addition, the above sensor can be used as a gas sensor, a molecular sensor, a solution sensor, a battery material, an artificial photosynthesis material, etc., and among these, it can be particularly suitably used as a gas sensor that shows a change in resistance value in response to combustible gases or reducing gases such as acetone, isoprene, toluene, ammonia, and hydrogen, oxidizing gases such as NO2 (nitrogen dioxide), or combustion-supporting gases such as NO2 (nitrogen dioxide).

[0045] Next, a gas sensor, which is a representative example of a sensor using the structure film or particles of the present invention, will be described. The sensor of the present invention has a substrate, a pair of electrodes provided on the substrate, and the structure film or particles formed on the electrodes.

[0046] When the sensor of the present invention is used as a gas sensor, it is preferable that the sensor shows a resistance change of 1.0 to 6.2 in response to a reducing gas (concentration 5 ppm) such as acetone, isoprene, toluene, ammonia, or hydrogen, or an oxidizing gas (concentration 5 ppm) such as nitrogen dioxide. It is also preferable that the sensor shows a resistance change of 1.0 to 1.8 in response to low concentration acetone (200 ppb). The sensor of the present invention shows a resistance change in response to these target gases and air.

[0047] Air is a mixed gas of 20% oxygen and 80% nitrogen. If the resistance of a gas sensor in air is expressed as Ra, and the resistance of the gas sensor in the target gas is expressed as Rg, the rate of change in electrical resistance (rate of resistance change) when switching from air to the target gas is expressed as Ra / Rg.

[0048] In addition, in a gas sensor using the structural film of this embodiment, when the resistance change with respect to acetone is compared with the resistance change with respect to isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide, an acetone selectivity of 1.0 or more and 5.1 or less is obtained.

[0049] According to the gas sensor of the above embodiment, a gas sensor is obtained that exhibits a resistance value change in the range of 2.7 or more and 6.2 or less as the sensor sensitivity to acetone, in the range of 1.5 or more and 2.6 or less as the sensor sensitivity to isoprene, in the range of 1.4 or more and 2.9 or less as the sensor sensitivity to toluene, in the range of 1.0 or more and 1.6 or less as the sensor sensitivity to ammonia, in the range of 1.0 or more and 1.4 or less as the sensor sensitivity to hydrogen, and in the range of 1.2 or more and 1.8 or less as the sensor sensitivity to nitrogen dioxide.

[0050] In addition, gas sensors can be obtained that exhibit resistance value changes in the range of 1 to 2.5 times the ratio of the sensor sensitivity to acetone to the sensor sensitivity to isoprene (the ratio of the sensor sensitivity to acetone divided by the sensor sensitivity to isoprene), 1 to 2.6 times the ratio of the sensor sensitivity to acetone to the sensor sensitivity to toluene (the ratio of the sensor sensitivity to acetone divided by the sensor sensitivity to toluene), 1 to 4.1 times the ratio of the sensor sensitivity to acetone to the sensor sensitivity to ammonia (the ratio of the sensor sensitivity to acetone divided by the sensor sensitivity to ammonia), 1 to 5.1 times the ratio of the sensor sensitivity to acetone to the sensor sensitivity to hydrogen (the ratio of the sensor sensitivity to acetone divided by the sensor sensitivity to hydrogen), and 1 to 4.5 times the ratio of the sensor sensitivity to acetone to the sensor sensitivity to nitrogen dioxide (the ratio of the sensor sensitivity to acetone divided by the sensor sensitivity to nitrogen dioxide).

[0051] A sensor element using a structural film made of a nickel-containing material can be manufactured by immersing a base material such as a substrate having a metal electrode in a solution containing nickel, and forming a structural film made of a nickel-containing material on the base material such as a substrate having a metal electrode.

[0052] In addition, a sensor element using a structural film made of a manganese-containing substance can be manufactured by immersing a base material such as a substrate provided with a metal electrode in a solution containing manganese, and forming a structural film made of a manganese-containing substance on the base material such as a substrate having a metal electrode.

[0053] Furthermore, a method for producing an element using a composite structure film made of a complex of a nickel-containing material and a manganese-containing material of the present invention can be performed by immersing a base material such as a substrate provided with a metal electrode in a solution containing nickel to form a structure film made of a nickel-containing material on the base material such as a substrate having a metal electrode, and subsequently immersing the base material in a solution containing manganese to form a composite structure film made of a manganese-containing material on the base material such as a substrate having a metal electrode. EXAMPLES

[0054] First, as Reference Example 1, a structural film made of a nickel-containing material was synthesized, as Reference Example 2, particles made of a nickel-containing material were synthesized, as Reference Example 3, a structural film made of a manganese-containing material was synthesized, and as Reference Example 4, particles made of a manganese-containing material were synthesized.

[0055] (Reference example 1) <Synthesis of structural films made of nickel-containing materials> 5mmol of urea and 1mmol of nickel chloride hexahydrate (NiCl2·6H2O) were added to a mixed solution of 60mL of distilled water and 20mL of ethanol, and then the mixture was dissolved by stirring at 300rpm for 30 minutes at room temperature using a magnetic stirrer. Next, the substrate was immersed in the above solution and kept at 84℃ for 6 hours, then naturally cooled, removed, washed with water, and naturally dried to obtain a structured film consisting of nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No.38-0715).

[0056] (Reference example 2) <Synthesis of particles made of nickel-containing materials> 5 mmol of urea and 1 mmol of nickel chloride hexahydrate (NiCl2·6H2O) were added to a mixed solution of 60 mL of distilled water and 20 mL of ethanol, and then the mixture was dissolved by stirring at 300 rpm for 30 minutes using a magnetic stirrer at room temperature. The solution was then kept at 84°C for 6 hours and allowed to cool naturally. After cooling, the particles were allowed to settle by leaving the solution and centrifuging it, the supernatant was removed, and the synthesized particles were collected to obtain particles consisting of nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No.38-0715).

[0057] (Reference example 3) <Synthesis of structural films made of manganese-containing materials> 0.04 mmol of potassium permanganate (KMnO4) was added to 100 mL of distilled water, and then the mixture was dissolved by stirring at 300 rpm for 30 minutes at room temperature using a magnetic stirrer. The substrate was immersed in the above solution and kept at 180°C for 12 and 24 hours, and then allowed to cool naturally. Next, the substrate was immersed in the above solution and kept at 150°C for 12 hours, and then allowed to cool naturally. After immersion, the substrate was taken out, washed with water, and allowed to dry naturally. The X-ray diffraction pattern of the resulting structured film on the substrate was assigned to manganese dioxide, MnO2 (JCPDS No. 14-0644). In addition, when the sensor characteristics of a structural film made of a manganese-containing material synthesized by holding it at 150℃ for 12 hours were evaluated, it showed a resistance value (Rg) of 216kΩ in air. On the other hand, it showed a low resistance value (Ra) of 200kΩ against 40ppb of acetone. From these, the resistance change rate (Ra / Rg) was 1.08.

[0058] (Reference example 4) <Synthesis of particles made of manganese-containing materials> 0.04 mmol of potassium permanganate (KMnO4) was added to 100 mL of distilled water, and then dissolved by stirring at 300 rpm for 30 minutes using a magnetic stirrer at room temperature. Next, the above solution was kept at 180°C for 12 hours and 24 hours, and then allowed to cool naturally. After cooling, the particles were allowed to settle by leaving the solution and centrifuging it, the supernatant was removed, and the particles were collected. The particles were composed of a material having a sheet-like morphology, and the X-ray diffraction pattern of the particles was assigned to manganese dioxide, MnO2 (JCPDS No. 14-0644).

[0059] Next, as Example 1, a composite structure film made of a composite of a nickel-containing material and a manganese-containing material was synthesized, and as Example 2, composite particles made of a composite of a nickel-containing material and a manganese-containing material were synthesized.

[0060] Example 1 <Synthesis of composite membranes consisting of nickel-containing and manganese-containing materials> First, a nickel-containing structural film was synthesized in the same manner as in Reference Example 1, as described below. <Synthesis of nickel-containing structural films> 5mmol of urea and 1mmol of nickel chloride hexahydrate (NiCl2·6H2O) were added to a mixed solution of 60mL of distilled water and 20mL of ethanol, and then the mixture was dissolved by stirring at 300rpm for 30 minutes using a magnetic stirrer at room temperature. Next, the substrate was immersed in the above solution and kept at 84℃ for 6 hours, then naturally cooled. After immersion, the substrate was taken out, washed with water, and naturally dried to form a film of nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No. 38-0715). Next, a manganese-containing structural film was synthesized by the following method. <Synthesis of manganese-containing structural membrane> 1.27 mmol of potassium permanganate (KMnO4) was added to 100 mL of distilled water, and then dissolved by stirring for 30 minutes at room temperature with a magnetic stirrer at 300 rpm. Next, the substrate on which the structural film made of the nickel-containing material was formed was immersed in this solution and kept at 65°C for 10 minutes, 30 minutes, 1 hour, 2 hours, and 4 hours, and then allowed to cool naturally. After immersion, the substrate was removed, washed with water, and air-dried to form a composite structure film consisting of a composite of nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No. 38-0715) and manganese dioxide, MnO2 (JCPDS No. 14-0644). <Heat treatment> Furthermore, after placing the substrate on which the film was formed in an electric furnace, the temperature was increased from room temperature to 400° C. in the atmosphere, and after heating at 400° C. for 5 hours, a heat treatment was performed in which the substrate was naturally cooled.

[0061] (Example 1-1) In the synthesis of the manganese-containing structure film in Example 1, a scanning electron microscope photograph of the composite structure film consisting of a composite of a nickel-containing material and a manganese-containing material obtained by immersing a substrate for 10 minutes is shown in Figure 1. From this photograph, it can be confirmed that the composite structure film consists of a sheet-like structure having a sheet-like form and a sheet-like structure laminate. Fig. 2 shows the size of the sheets (sheet-like structure and sheet-like structure laminate) measured using Fig. 1. The number of sheets laminated, the presence or absence of branches, and the size are as shown in Table 1 below.

[0062] [Table 1]

[0063] Here, the aspect ratio in this embodiment is a value obtained by dividing the length in the longitudinal direction by the thickness. From the above results, the minimum number of laminated layers was 1, the maximum was 3, and the range was 1 to 3. The minimum lengthwise dimension was 30 nm, the maximum was 400 nm, and the range was 30 to 400 nm, the minimum thickness was 5 nm, the maximum was 20 nm, and the range was 5 to 20 nm. The minimum aspect ratio was 3, the maximum was 40, and the range was 3 to 40.

[0064] In this embodiment, the composite-structure membrane is composed of a sheet-like structure having a sheet-like form and a sheet-like structure laminate. The "sheet-like form" here means a form in which the thickness is a fraction or less of the longitudinal direction. More specifically, as shown above, the minimum value of the aspect ratio was 3, the maximum value was 40, and the range was 3 to 40.

[0065] (Example 1-2) 3 shows a scanning electron microscope photograph of the composite structure film consisting of a composite of a nickel-containing material and a manganese-containing material obtained by immersing a substrate for 4 hours in the synthesis of the manganese-containing structure film in Example 1. From this photograph, it can be confirmed that the composite structure film consists of a sheet-like structure and a sheet-like structure laminate having a sheet-like form, and that the sheet is curved. Moreover, Fig. 4 shows the size of the sheets (sheet-like structure and sheet-like structure laminate) measured using Fig. 3. The respective sizes were as shown in Table 2 below.

[0066] [Table 2]

[0067] From the above results, the minimum value in the longitudinal direction was 20 nm, the maximum value was 250 nm, and the range was 20 nm to 250 nm, the minimum value of the thickness was 5 nm, the maximum value was 30 nm, and the range was 5 nm to 30 nm, and the minimum value of the aspect ratio was 4, the maximum value was 30, and the range was 4 to 30.

[0068] In this embodiment, the composite-structure membrane was composed of a sheet-like structure and a sheet-like structure laminate having a sheet-like form, and also contained a curved sheet. The "sheet-like form" here means a form in which the thickness is a fraction or less of the longitudinal direction. More specifically, as shown above, the minimum value of the aspect ratio was 4, the maximum value was 30, and the range was 4 to 30.

[0069] (Examples 1-3) 5 shows a scanning electron microscope photograph of the composite-structure film consisting of a composite of a nickel-containing substance and a manganese-containing substance obtained by immersing a substrate for 24 hours in the synthesis of the manganese-containing structure film in Example 1. From this photograph, it can be confirmed that the composite-structure film consists of a sheet-like structure having a sheet-like form, and that it is a sheet-like structure laminate having a hierarchical structure of small and large sheets. Moreover, Fig. 6 shows the size of the sheets (sheet-like structure and sheet-like structure laminate) measured using Fig. 5. The sheet sizes were as shown in Table 3 below.

[0070] [Table 3]

[0071] From the above results, the minimum value in the longitudinal direction was 20 nm, the maximum value was 250 nm, and the range was 20 nm to 250 nm, the minimum value of the thickness was 5 nm, the maximum value was 30 nm, and the range was 5 nm to 30 nm, and the minimum value of the aspect ratio was 4, the maximum value was 30, and the range was 4 to 30. In addition, large sheets with sizes such as "240 nm in the longitudinal direction, 50 nm in thickness, and an aspect ratio of 4.8" and "330 nm in the longitudinal direction, 35 nm in thickness, and an aspect ratio of 9.4" were composed of small sheets with sizes such as "30 nm in the longitudinal direction, 1 nm in thickness, and an aspect ratio of 30" and "25 nm in the longitudinal direction, 5 nm in thickness, and an aspect ratio of 5", forming a hierarchical structure of small and large sheets.

[0072] In this embodiment, the composite-structure membrane is composed of a sheet-like structure and a sheet-like structure laminate having a sheet-like form, and is a sheet-like structure laminate having a hierarchical structure of small sheets and large sheets. The "sheet-like form" here means a form in which the thickness is a fraction or less of the longitudinal direction. More specifically, as shown above, the minimum value of the aspect ratio was 4, the maximum value was 30, and the range was 4 to 30.

[0073] <Shape and size range in Example 1> When the ranges of shapes and sizes in Examples 1-1 to 1-3 were confirmed, the ranges of shapes and sizes for the composite-structure membrane made of a composite of a nickel-containing material and a manganese-containing material were as follows. Shape: Sheet shape, curved, sometimes with a hierarchical structure of small and large sheets Number of layers: 1 to 3 Longitudinal range: 20nm~400nm Thickness range: 5nm~30nm Aspect ratio range: 3~40

[0074] Example 2 <Synthesis of composite particles consisting of a composite of nickel-containing material and manganese-containing material> First, in the same manner as in Reference Example 2, a nickel-containing structural film was synthesized as follows. <Synthesis of particles made of nickel-containing materials> 5 mmol of urea and 1 mmol of nickel chloride hexahydrate (NiCl2·6H2O) were added to a mixed solution of 60 mL of distilled water and 20 mL of ethanol, and then the mixture was dissolved by stirring at 300 rpm for 30 minutes at room temperature using a magnetic stirrer. Next, the above solution was kept at 84℃ for 6 hours and then allowed to cool naturally. After cooling, the particles were allowed to settle by leaving them or centrifuging, and the supernatant was removed to obtain composite particles of nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No.38-0715). Next, the particles made of the nickel-containing substance were further immersed in an aqueous manganese-containing solution to synthesize composite particles made of a composite of the nickel-containing substance and the manganese-containing substance. <Synthesis of particles made of manganese-containing materials> 1.27 mmol of potassium permanganate (KMnO4) was added to 100 mL of distilled water, and then the mixture was dissolved by stirring at room temperature for 30 minutes at 300 rpm using a magnetic stirrer. The particles made of the nickel-containing material were immersed in the above solution and held at 65°C for 10 minutes, 30 minutes, 1 hour, 2 hours, and 4 hours, respectively, and then allowed to cool naturally. After cooling, the particles were allowed to settle by leaving them alone or by centrifugation, and the supernatant was removed to recover composite particles made of a composite of the nickel-containing material and the manganese-containing material. <Heat treatment> Furthermore, after placing the particles in an electric furnace, the temperature was increased from room temperature to 400° C. in the atmosphere, and after heating at 400° C. for 5 hours, the particles were naturally cooled for heat treatment.

[0075] (Example 2-1) 7 shows a scanning electron microscope photograph of composite particles made of a composite of a nickel-containing substance and a manganese-containing substance, which were obtained by immersing the particles in the manganese-containing solution for 10 minutes in the synthesis of the composite particles in Example 2. From this photograph, it can be confirmed that the composite particles are made of a sheet-like structure and a sheet-like structure laminate having a sheet-like form. Moreover, Fig. 8 shows the size of the sheets (sheet-like structure and sheet-like structure laminate) measured using Fig. 7. The sheet sizes were as shown in Table 4 below.

[0076] [Table 4]

[0077] From the above results, the minimum value in the longitudinal direction was 100 nm, the maximum value was 1800 nm, and the range was 100 nm to 1800 nm, and the minimum value of the thickness was 10 nm, the maximum value was 100 nm, and the range was 10 nm to 100 nm. The minimum value of the aspect ratio was 5, the maximum value was 34, and the range was 5 to 34. In addition, when the sheet 1 with an unclear thickness (thickness less than 10 nm) was included, the maximum value of the aspect ratio was greater than 180.

[0078] That is, the ranges of shapes and sizes in Example 2-1 were as follows: Shape: Sheet shape Longitudinal range: 100nm~1800nm Thickness range: 10nm~100nm Aspect ratio range: 5~34 Including sheet 1, whose thickness is unclear (thickness is less than 10 nm), Aspect ratio range: 5~180

[0079] Various evaluations were carried out based on the above Reference Examples 1 and 2 and Examples 1 and 2 below. Example 3 <X-ray diffraction evaluation of a structured film made of nickel-containing material and a composite structured film made of a composite of a nickel-containing material and a manganese-containing material> The structure film made of the nickel-containing material synthesized in Reference Example 1 and the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 were evaluated by X-ray diffraction. The X-ray diffraction patterns are shown in FIG.

[0080] In FIG. 9, the bottom row is an X-ray diffraction pattern of a structural film made of a nickel-containing material synthesized in Reference Example 1, and the rows other than the bottom row are X-ray diffraction patterns of composite structural films made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1. The X-ray diffraction pattern of the structural film made of the nickel-containing material synthesized in Reference Example 1 was assigned to nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No. 38-0715).

[0081] All rows except the bottom row are X-ray diffraction patterns of composite structure films consisting of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1, and the second, third, fourth, fifth, sixth, seventh, and eighth rows from the bottom are X-ray diffraction patterns of samples in which the synthesis time of the manganese-containing film was changed to 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 6 hours, and 24 hours, respectively. The X-ray diffraction pattern of the composite structure film composed of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 was assigned to nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No. 38-0715) and manganese dioxide, MnO2 (JCPDS No. 14-0644).

[0082] Example 4 <X-ray diffraction evaluation of a structured film made of a nickel-containing material and a composite structured film made of a composite of a nickel-containing material and a manganese-containing material after heat treatment> The structure film made of the nickel-containing material synthesized in Reference Example 1 and the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 were evaluated by X-ray diffraction after heat treatment at 400°C for 5 hours in air. Figure 10 shows the X-ray diffraction patterns.

[0083] The bottom row shows the X-ray diffraction pattern of the structural film made of the nickel-containing material synthesized in Reference Example 1 after heat treatment at 400° C. for 5 hours in air. The X-ray diffraction pattern of the structural film made of the nickel-containing material synthesized in Reference Example 1 after heat treatment at 400° C. for 5 hours in air was attributed to nickel monoxide, NiO (JCPDS No. 65-2901).

[0084] Moreover, all but the bottom row are X-ray diffraction patterns of the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 after heat treatment in air at 400°C for 5 hours, and the second, third, fourth, fifth, sixth, seventh, and eighth rows from the bottom are X-ray diffraction patterns of samples in which the synthesis time of the manganese-containing film was changed to 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 6 hours, and 24 hours, respectively. The X-ray diffraction pattern of the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 after heat treatment in air at 400°C for 5 hours was assigned to nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No. 38-0715) and manganese dioxide, MnO2 (JCPDS No. 14-0644).

[0085] This is because manganese dioxide, MnO2 (JCPDS No. 14-0644), which was present before heating, reacted with a portion of nickel hydroxide 0.75 hydrate, Ni(OH)2·0.75H2O (JCPDS No. 38-0715), to form manganese nickel oxide, (Mn 0.66 Ni 0.34 )O (JCPDS No. 81-9152). It is also believed that a portion of nickel hydroxide 0.75 hydrate, Ni(OH)2 0.75H2O (JCPDS No. 38-0715), underwent a phase transition to NiO (JCPDS No. 65-2901) upon heat treatment.

[0086] As the synthesis time of the manganese-containing film is increased, the half-width of each peak in the X-ray diffraction pattern increases. For example, the half-width of each peak in the X-ray diffraction pattern of a film synthesized for 4 hours is wider than that of a film synthesized for 10 minutes.

[0087] This is because the amount of manganese dioxide, MnO2 (JCPDS No. 14-0644), produced increases with the synthesis time of the manganese-containing film, and the amount of manganese nickel oxide, MnO2 (JCPDS No. 14-0644), produced increases with the synthesis time of the manganese-containing film.0.66 Ni 0.34 )O (JCPDS No. 81-9152) was also produced. 0.66 Ni 0.34 )O (JCPDS No. 81-9152) was produced, which resulted in the production of manganese nickel oxide, (Mn 0.66 Ni 0.34 The intensity of the diffraction lines from nickel monoxide, NiO (JCPDS No. 65-2901) and manganese nickel oxide, (Mn 0.66 Ni 0.34 This is thought to be due to the broadening of the half-width in the diffraction peaks where the diffraction lines of )O (JCPDS No. 81-9152) overlap.

[0088] Example 5 The composition of the nano-structured particles made of the nickel-containing material synthesized in Reference Example 2 and the composite structure particles made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 2 were evaluated by X-ray photoelectron spectroscopy (XPS). The compositions are shown in FIG.

[0089] In the nano-structured particles made of a nickel-containing substance synthesized in Reference Example 2, since manganese is not contained in the raw material, the manganese content is 0 mol %, and the molar ratio of manganese to nickel is also 0.

[0090] In addition, the composition of the composite structure particles composed of a composite of the nickel-containing material and the manganese-containing material synthesized in Example 2 (immersion times in the manganese-containing solution: 10 minutes, 30 minutes, 1 hour, 2 hours, and 4 hours) was evaluated by X-ray photoelectron spectroscopy (XPS), and the molar ratios of manganese to nickel were found to be 0.17, 0.21, 0.25, 0.66, and 0.83, respectively.

[0091] For the composite structure particles made of a composite of a nickel-containing substance and a manganese-containing substance synthesized in Example 2, the molar ratio of manganese to nickel ranged from a minimum of 0.17 to a maximum of 0.83.

[0092] The only difference between Reference Example 1 and Reference Example 2, and between Example 1 and Example 2, is the presence or absence of a substrate. From these, the range of the molar ratio of manganese to nickel in the composite-structure film made of the composite of the nickel-containing substance and the manganese-containing substance synthesized in Example 1 is estimated to be a minimum of 0.17 and a maximum of 0.83.

[0093] In addition, for the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1, the molar ratio of manganese to nickel is estimated to be in the range of 0.17 to 0.83.

[0094] Example 6 <Gas sensor characteristic evaluation> The sensor sensitivity to various gases was measured for the structure film made of the nickel-containing material synthesized in Reference Example 1 and the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1. The results are shown in FIG.

[0095] The immersion times in the manganese-containing solution were set to 10 minutes, 30 minutes, 1 hour, 2 hours, and 4 hours, respectively, to form the structural films of Reference Example 1 and Example 1 on the surface of an aluminum oxide substrate on which a platinum electrode had been printed.

[0096] The concentrations of acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide were all set to 5 ppm. In addition, the sensor substrate temperature was set to 225°C by applying a voltage to a platinum heater printed on the sensor substrate.

[0097] A multi-component gas mixer (MU-3000 series) manufactured by Horiba Estec Co., Ltd. was used to adjust and mix the gases. Nitrogen, oxygen, acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide were used from gas cylinders. As the above gases were from gas cylinders, they contained no moisture and the humidity was 0%.

[0098] First, air was passed, then the gas to be detected, such as acetone, was passed, and then air was passed again. The air was a mixture of 20% oxygen and 80% nitrogen. The concentration of the gas to be detected, such as acetone, was 5 ppm, and the mixture was 20% oxygen and 80% nitrogen.

[0099] The resistance in air was measured immediately before switching from air to the target gas, such as acetone. This resistance value was taken as Ra, and the rate of change in electrical resistance when switching from air to the target gas (resistance change rate, sensor sensitivity) was taken as Ra / Rg.

[0100] The resistance change rate was calculated from Ra / Rg for acetone, isoprene, toluene, ammonia, and hydrogen, which are reducing gases, and for nitrogen dioxide, which is an oxidizing gas, the resistance change rate was calculated from Ra / Rg.

[0101] The electrical resistance between the platinum electrodes changed in the presence of any of the target gases: acetone, isoprene, toluene, ammonia, hydrogen, or nitrogen dioxide. This confirmed that the sensor element was capable of detecting acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide based on the change in electrical resistance.

[0102] (Nickel oxide film sensor) In the sensor with the structural film made of the nickel-containing material synthesized in Reference Example 1, the sensor sensitivity (Rg / Ra) to acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide (all at a concentration of 5 ppm, sensor element temperature of 225°C) was 2.71, 1.58, 1.54, 1.06, 1.06, and 1.42, respectively.

[0103] From these results, the ratio of the sensor sensitivity to acetone to that to isoprene was 1.72, the ratio of the sensor sensitivity to acetone to that to toluene was 1.76, the ratio of the sensor sensitivity to acetone to that to ammonia was 2.65, the ratio of the sensor sensitivity to acetone to that to hydrogen was 2.65, and the ratio of the sensor sensitivity to acetone to that to nitrogen dioxide was 1.92.

[0104] From the above, the sensor sensitivity was within the range of 1.06 to 2.71, and the ratio of the sensor sensitivity to acetone was within the range of 1.72 to 2.65.

[0105] (Nickel oxide film / manganese nickel oxide film laminated sensor (immersed in manganese-containing solution for 10 minutes)) In the sensor of the composite structure film (immersion time in the manganese-containing solution: 10 minutes) made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1, the sensor sensitivity (Rg / Ra) to acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide (all at a concentration of 5 ppm, sensor element temperature of 225°C) was 3.28, 2.18, 1.75, 1.27, 1.11, and 1.41, respectively.

[0106] From these results, the ratio of the sensor sensitivity to acetone to that to isoprene was 1.51, the ratio of the sensor sensitivity to acetone to that to toluene was 1.88, the ratio of the sensor sensitivity to acetone to that to ammonia was 2.58, the ratio of the sensor sensitivity to acetone to that to hydrogen was 2.95, and the ratio of the sensor sensitivity to acetone to that to nitrogen dioxide was 2.32.

[0107] From the above, the sensor sensitivity was within the range of 1.11 to 3.28, and the ratio of the sensor sensitivity to acetone was within the range of 1.51 to 2.95.

[0108] (Nickel oxide film / manganese nickel oxide film laminated sensor (immersed in manganese-containing solution for 30 minutes)) In the sensor of the composite structure film (immersion time in the manganese-containing solution: 30 minutes) made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1, the sensor sensitivity (Rg / Ra) to acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide (all at a concentration of 5 ppm, sensor element temperature of 225°C) was 3.60, 2.04, 1.49, 1.13, 1.10, and 1.73, respectively.

[0109] From these results, the ratio of the sensor sensitivity to acetone to that to isoprene was 1.77 times, the ratio of the sensor sensitivity to acetone to that to toluene was 2.41 times, the ratio of the sensor sensitivity to acetone to that to ammonia was 3.19 times, the ratio of the sensor sensitivity to acetone to that to hydrogen was 3.29 times, and the ratio of the sensor sensitivity to acetone to that to nitrogen dioxide was 2.08 times.

[0110] From the above, the sensor sensitivity was within the range of 1.10 to 3.60, and the ratio of the sensor sensitivity to acetone was within the range of 1.77 to 3.29.

[0111] (Nickel oxide film / manganese nickel oxide film laminated sensor (immersed in manganese-containing solution for 1 hour)) In the sensor of the composite structure film (immersion time in manganese-containing solution: 1 hour) made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1, the sensor sensitivity (Rg / Ra) to acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide (all at a concentration of 5 ppm, sensor element temperature of 225°C) was 2.79, 2.26, 2.83, 1.13, 1.33, and 1.27, respectively.

[0112] From these results, the ratio of the sensor sensitivity to acetone to that to isoprene was 1.23 times, the ratio of the sensor sensitivity to acetone to that to toluene was 0.99 times, the ratio of the sensor sensitivity to acetone to that to ammonia was 2.47 times, the ratio of the sensor sensitivity to acetone to that to hydrogen was 2.10 times, and the ratio of the sensor sensitivity to acetone to that to nitrogen dioxide was 2.20 times.

[0113] From the above, the sensor sensitivity was within the range of 1.19 to 2.83, and the ratio of the sensor sensitivity to acetone was within the range of 0.99 to 2.20.

[0114] (Nickel oxide film / manganese nickel oxide film laminated sensor (soaked in manganese-containing solution for 2 hours)) In the sensor of the composite structure film (immersion time in the manganese-containing solution: 2 hours) made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1, the sensor sensitivity (Rg / Ra) to acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide (all at a concentration of 5 ppm, sensor element temperature of 225°C) was 3.98, 2.27, 2.21, 1.51, 1.25, and 1.34, respectively.

[0115] From these results, the ratio of the sensor sensitivity to acetone to that to isoprene was 1.76, the ratio of the sensor sensitivity to acetone to that to toluene was 1.80, the ratio of the sensor sensitivity to acetone to that to ammonia was 2.64, the ratio of the sensor sensitivity to acetone to that to hydrogen was 3.19, and the ratio of the sensor sensitivity to acetone to that to nitrogen dioxide was 2.97.

[0116] From the above, the sensor sensitivity was within the range of 1.25 to 3.98, and the ratio of the sensor sensitivity to acetone was within the range of 1.76 to 3.19.

[0117] (Nickel oxide film / manganese nickel oxide film laminated sensor (immersed in manganese-containing solution for 4 hours)) In the sensor of the composite structure film (immersion time in the manganese-containing solution: 4 hours) made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1, the sensor sensitivity (Rg / Ra) to acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide (all at a concentration of 5 ppm, sensor element temperature of 225°C) was 6.15, 2.54, 2.43, 1.52, 1.23, and 1.40, respectively.

[0118] From these results, the ratio of the sensor sensitivity to acetone to that to isoprene was 2.43 times, the ratio of the sensor sensitivity to acetone to that to toluene was 2.53 times, the ratio of the sensor sensitivity to acetone to that to ammonia was 4.04 times, the ratio of the sensor sensitivity to acetone to that to hydrogen was 5.01 times, and the ratio of the sensor sensitivity to acetone to that to nitrogen dioxide was 4.40 times.

[0119] From the above, the sensor sensitivity was within the range of 1.23 to 6.15, and the ratio of the sensor sensitivity to acetone was within the range of 2.43 to 5.01.

[0120] (Acetone sensor sensitivity range) The sensor with the highest sensitivity to acetone was the composite structure membrane made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 4 hours), and the value was 6.15. The sensor with the lowest sensitivity to acetone was the structural film made of the nickel-containing material synthesized in Example 1, with a value of 2.71. From these results, the sensor sensitivity to acetone was in the range of 2.7 to 6.2.

[0121] When limited to composite structure films made of a composite of a nickel-containing material and a manganese-containing material, the sensor with the lowest sensor sensitivity to acetone was the composite structure film made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1 (immersion time in a manganese-containing solution: 1 hour), with a value of 2.79. From these results, when limited to composite structure films made of a composite of a nickel-containing material and a manganese-containing material, the sensor sensitivity to acetone was within the range of 2.7 to 6.2.

[0122] (sensor sensitivity range for isoprene) The sensor with the highest sensitivity to isoprene was the composite structure membrane made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 4 hours), and the value was 2.54. The sensor with the lowest sensitivity to isoprene was the structural film made of the nickel-containing material synthesized in Example 1, and the value was 1.58. From these results, the sensor sensitivity to isoprene was in the range of 1.5 to 2.6.

[0123] Looking only at the composite structure films made of a complex of a nickel-containing material and a manganese-containing material, the sensor with the lowest sensor sensitivity to isoprene was the composite structure film made of a complex of a nickel-containing material and a manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 30 minutes), and the value was 2.04. In the case of the composite structure film consisting of a composite of a nickel-containing material and a manganese-containing material, the sensor sensitivity to isoprene was in the range of 2.0 to 2.6.

[0124] (Sensor sensitivity range for toluene) The sensor with the highest sensitivity to toluene was the composite structure membrane made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 1 hour), and the value was 2.83. The sensor with the lowest sensitivity to toluene was the composite structure film (immersion time in manganese-containing solution: 30 minutes) made of the composite of the nickel-containing material and manganese-containing material synthesized in Example 1, and the value was 1.49. From these results, the sensor sensitivity to toluene was in the range of 1.4 to 2.9.

[0125] (Ammonia sensor sensitivity range) The sensor with the highest sensitivity to ammonia was the composite structure membrane made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 4 hours), and the value was 1.52. The sensor with the lowest sensitivity to ammonia was the structural film made of the nickel-containing material synthesized in Example 1, and the value was 1.06. From these results, the sensor sensitivity to ammonia was in the range of 1.0 to 1.6.

[0126] Looking only at the composite structure films made of a composite of a nickel-containing material and a manganese-containing material, the sensor with the lowest sensor sensitivity to ammonia was the composite structure film made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 30 minutes), and the value was 1.13. In the case of the composite structure film consisting of a composite of a nickel-containing material and a manganese-containing material, the sensor sensitivity to ammonia was in the range of 1.1 to 1.6.

[0127] (Sensor sensitivity range for hydrogen) The sensor with the highest sensitivity to hydrogen was the composite structure membrane made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 1 hour), and the value was 1.33. The sensor with the lowest sensitivity to hydrogen was the structural film made of the nickel-containing material synthesized in Example 1, and the value was 1.06. From these results, the sensor sensitivity to hydrogen was in the range of 1.0 to 1.4.

[0128] Looking only at the composite structure films made of a composite of a nickel-containing material and a manganese-containing material, the sensor with the lowest sensor sensitivity to hydrogen was the composite structure film made of a composite of a nickel-containing material and a manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 30 minutes), and the value was 1.10. In the case of the composite structure film consisting of a composite of a nickel-containing material and a manganese-containing material, the sensor sensitivity to hydrogen was in the range of 1.0 to 1.4.

[0129] (Sensor sensitivity range for nitrogen dioxide) The sensor with the highest sensitivity to nitrogen dioxide was the composite structure membrane made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 30 minutes), and the value was 1.73. The sensor with the lowest sensitivity to nitrogen dioxide was the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 1 hour), with a value of 1.27. From these results, the sensor sensitivity to nitrogen dioxide was in the range of 1.2 to 1.8.

[0130] (The sensor with the highest sensor sensitivity is the one with the highest ratio of sensor sensitivity to acetone to each gas.) For each of the gases, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide, the sensor with the highest sensor sensitivity, in terms of the ratio of sensor sensitivity to acetone to that of each gas, was the composite structure membrane made of the composite of the nickel-containing material and manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 4 hours).

[0131] The sensor sensitivity ratios, as described above, were as follows: The ratio of the sensor sensitivity to acetone to that to isoprene was 2.43, the ratio of the sensor sensitivity to acetone to that to toluene was 2.53, the ratio of the sensor sensitivity to acetone to that to ammonia was 4.04, the ratio of the sensor sensitivity to acetone to that to hydrogen was 5.01, and the ratio of the sensor sensitivity to acetone to that to nitrogen dioxide was 4.40.

[0132] Acetone selectivity can fall to a minimum of 1 due to the presence of other flammable gases, the presence of moisture, sensor degradation causing a decrease in responsiveness, or a decrease in responsiveness when the sensor temperature is low. At a minimum of 1, the change in resistance to acetone is the same as the change in resistance to isoprene, toluene, ammonia, hydrogen, nitrogen dioxide, etc., and the two are indistinguishable. With this sensor, too, the acetone selectivity can fall within the following ranges when the above operating conditions are applied.

[0133] The ratio of the sensor sensitivity to acetone to the sensor sensitivity to isoprene can range from 1 to 2.43 times, the ratio of the sensor sensitivity to acetone to the sensor sensitivity to toluene can range from 1 to 2.53 times, the ratio of the sensor sensitivity to acetone to the sensor sensitivity to ammonia can range from 1 to 4.04 times, the ratio of the sensor sensitivity to acetone to the sensor sensitivity to hydrogen can range from 1 to 5.01 times, and the ratio of the sensor sensitivity to acetone to the sensor sensitivity to nitrogen dioxide can range from 1 to 4.40 times.

[0134] (Sensor sensitivity to low concentration acetone 200 ppb) The sensor sensitivity to a low concentration of acetone of 200 ppb at each sensor element temperature was measured for the composite structure film (immersion time in manganese-containing solution: 10 minutes, 30 minutes, 1 hour, 2 hours, 4 hours) made of the composite of nickel-containing material and manganese-containing material synthesized in Example 1. The results are shown in Figure 13.

[0135] For the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 10 minutes), the sensor sensitivity was 1.1, 1.4, 1.7, 1.6, 1.3, and 1.1 when the sensor element temperature was changed to 175°C, 200°C, 225°C, 250°C, 275°C, and 300°C, respectively.

[0136] For the composite structure film made of a composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 30 minutes), the sensor sensitivity was 1.1, 1.5, 1.7, 1.5, 1.3, and 1.2 when the sensor element temperature was changed to 175°C, 200°C, 225°C, 250°C, 275°C, and 300°C, respectively.

[0137] For the composite structure film made of a composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 1 hour), the sensor sensitivity was 1.0, 1.6, 1.8, 1.7, 1.6, and 1.4 when the sensor element temperature was changed to 175°C, 200°C, 225°C, 250°C, 275°C, and 300°C, respectively.

[0138] For the composite structure film made of a composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 2 hours), the sensor sensitivity was 1.1, 1.8, 1.8, 1.5, 1.4, and 1.2 when the sensor element temperature was changed to 175°C, 200°C, 225°C, 250°C, 275°C, and 300°C, respectively.

[0139] For the composite structure film made of the composite of the nickel-containing material and the manganese-containing material synthesized in Example 1 (immersion time in the manganese-containing solution: 4 hours), the sensor sensitivity was 1.5, 1.5, 1.7, 1.6, 1.6, and 1.4 when the sensor element temperature was changed to 175°C, 200°C, 225°C, 250°C, 275°C, and 300°C, respectively.

[0140] A high sensor sensitivity of minimum 1.0 to maximum 1.8 was observed in the sensor temperature range of 175° C. to 300° C. Furthermore, in the more preferable sensor temperature range of 200° C. to 250° C., an even higher sensor sensitivity of minimum 1.4 to maximum 1.8 was observed. In all sensors, the highest sensor sensitivity was observed at a sensor element temperature of 225° C. The sensor sensitivity at a sensor element temperature of 225° C. ranged from a minimum of 1.7 to a maximum of 1.8.

[0141] For comparison, in the catalog for the TGS2602, a representative semiconductor gas sensor manufactured by Figaro Engineering Co., Ltd., Rs / Ro=0.80 at 10 ppm hydrogen, where Rs=sensor resistance in gases of various concentrations and Ro=sensor resistance in clean air. Converting this to Ra / Rg gives the reciprocal of 0.80, Ra / Rg=1.25.

[0142] The sensor sensitivity of the composite structure film (immersion time in manganese-containing solution: 1 hour) made of a composite of nickel-containing material and manganese-containing material synthesized in Example 1 to 5 ppm of hydrogen was 1.33, which was 1.07 times higher than that of TGS2602 manufactured by Figaro Engineering Co., Ltd., despite the hydrogen concentration being half. Assuming that the sensor sensitivity is proportional to the hydrogen concentration in the hydrogen concentration range of 5 ppm to 10 ppm, the sensor sensitivity to 10 ppm of hydrogen in the composite structure film (immersion time in manganese-containing solution: 1 hour) made of the composite of nickel-containing material and manganese-containing material synthesized in Example 1 is calculated to be 1.66, which is twice the increase from 1 to 1.33. This is calculated as a sensor sensitivity 1.33 times higher than that of TGS2602 manufactured by Figaro Engineering Co., Ltd.

[0143] Although the type of gas was different, the sensor sensitivity to 5 ppm of acetone in the composite structure film (immersion time in manganese-containing solution: 4 hours) made of a composite of nickel-containing material and manganese-containing material synthesized in Example 1 was 6.15, which was 4.92 times higher than that of TGS2602 manufactured by Figaro Engineering Co., Ltd., despite the gas concentration being half.

[0144] Assuming that the sensor sensitivity is proportional to the acetone concentration in the range of acetone concentration from 5 ppm to 10 ppm, the sensor sensitivity to 10 ppm of acetone in the composite structure film (immersion time in manganese-containing solution: 4 hours) composed of the composite of nickel-containing material and manganese-containing material synthesized in Example 1 is calculated to be 11.3, which is twice the increase from 1 to 6.15. This is calculated to be 9.04 times higher than the value of TGS2602 manufactured by Figaro Engineering Co., Ltd.

[0145] The website for the product TGS2602 is shown as Non-Patent Document 1, and the website for the catalog for the product TGS2602 is shown as Non-Patent Document 2.

Claims

1. A structural film comprising a composite of a nickel-containing substance and a manganese-containing substance, and formed by bonding together in a crystal-grown state a sheet-like structure and / or a sheet-like structure laminate in which the sheet-like structures are laminated and the number of laminated sheets is two or more, The sheet-like structure and / or the sheet-like structure laminate, The longitudinal length L (nm) is in the range of 20 to 400 nm, The thickness T (nm) ranges from 5 to 30 nm; A structure film characterized in that the ratio R (aspect ratio: L / T) of the longitudinal length L (nm) to the thickness T (nm) is in the range of 3 to 40.

2. 2. The structure film according to claim 1, wherein the molar ratio of manganese to nickel in the structure film is 0.17 or more and 0.83 or less, or the molar ratio of nickel to manganese in the structure film is 0.17 or more and 0.83 or less.

3. A particle comprising a composite of a nickel-containing material and a manganese-containing material, characterized in that the sheet-like structure having a sheet-like form and / or the sheet-like structure laminate, in which the sheet-like structures are stacked and the number of stacked layers is two or more, is bonded in a crystal-grown state.

4. 4. The particle according to claim 3, wherein the molar ratio of manganese to nickel in the particle is 0.17 or more and 0.83 or less, or the molar ratio of nickel to manganese in the particle is 0.17 or more and 0.83 or less.

5. The sheet-like structure and / or the sheet-like structure laminate in the particle, The longitudinal length L (nm) is in the range of 100 to 1800 nm, The thickness T (nm) is in the range of 10 to 100 nm, 5. The particle according to claim 3, wherein the ratio R (aspect ratio: L / T) of the longitudinal length L (nm) to the thickness T (nm) is in the range of 5 to 34.

6. A method for producing a structural film comprising a composite of a nickel-containing material and a manganese-containing material, a sheet-like structure having a sheet-like form and / or a sheet-like structure laminate in which the sheet-like structures are stacked and the number of stacked layers is two or more, and which is bonded in a crystal-grown state, the method comprising: immersing a substrate in a solution containing at least nickel element to cause nucleation and crystal growth of the sheet-like structure made of a nickel-containing material on the substrate surface; forming a structural film composed of the sheet-like structure and the sheet-like structure laminate made of the nickel-containing material on the substrate; A method for producing a structure film, characterized in that the substrate is immersed in a solution containing at least manganese element, thereby causing nucleation and crystal growth of the sheet-like structure made of a manganese-containing material on the substrate surface, and a composite structure film consisting of the sheet-like structure and the sheet-like structure laminate, which is made of a complex of the nickel-containing material and the manganese-containing material, is formed.

7. A method for producing a structural film comprising a composite of a nickel-containing material and a manganese-containing material, a sheet-like structure having a sheet-like form and / or a sheet-like structure laminate in which the sheet-like structures are stacked and the number of stacked layers is two or more, and which is bonded in a crystal-grown state, the method comprising: immersing a substrate in a solution containing at least manganese element to cause nucleation and crystal growth of the sheet-like structure made of a manganese-containing material on the substrate surface; forming a structural film composed of the sheet-like structure and the sheet-like structure laminate made of the manganese-containing material on the substrate, A method for producing a structure film, characterized in that nucleation and crystal growth of the sheet-like structure made of a nickel-containing material are carried out on the surface of the substrate by immersing the substrate in a solution containing at least nickel element, and a composite structure film is formed consisting of the sheet-like structure and the sheet-like structure laminate, which is made of a composite of the manganese-containing material and the nickel-containing material.

8. 6. A method for producing particles according to claim 3, comprising the steps of: holding a solution containing at least nickel element at a predetermined temperature for a predetermined time, and then allowing it to cool, thereby carrying out nucleation and crystal growth of the sheet-like structure made of a nickel-containing substance; forming particles composed of the sheet-like structure and the sheet-like structure laminate made of the nickel-containing substance; and then: The method for producing particles is characterized in that the particles are kept in a solution containing at least manganese element at a predetermined temperature for a predetermined time and then allowed to cool, thereby causing nucleation and crystal growth of the sheet-like structure made of a manganese-containing material, and forming composite particles composed of the sheet-like structure and the sheet-like structure laminate, which are made of a complex of the nickel-containing material and the manganese-containing material.

9. 6. A method for producing particles according to claim 3, comprising the steps of: maintaining a solution containing at least manganese element at a predetermined temperature for a predetermined time, and then allowing it to cool, thereby carrying out nucleation and crystal growth of the sheet-like structure made of a manganese-containing substance; forming particles composed of the sheet-like structure and the sheet-like structure laminate made of the manganese-containing substance; and then: The method for producing particles is characterized in that the particles are kept in a solution containing at least nickel element at a predetermined temperature for a predetermined time and then allowed to cool, thereby causing nucleation and crystal growth of the sheet-like structure made of a nickel-containing material, and forming composite particles composed of the sheet-like structure and the sheet-like structure laminate, which are made of a composite of the manganese-containing material and the nickel-containing material.

10. A substrate; A pair of electrodes provided on the substrate; a structured film according to claim 1 or 2 formed on the electrode, and / or particles according to any one of claims 3 to 5; A sensor comprising:

11. A substrate, A pair of electrodes provided on the substrate; a structure film formed on the electrode, and / or a particle according to any one of claims 3 to 5; A gas sensor having The structure film includes a composite of a nickel-containing substance and a manganese-containing substance, and is configured by bonding a sheet-like structure having a sheet-like form and / or a sheet-like structure laminate having two or more laminated sheets of the sheet-like structures in a crystal-grown state, A gas sensor that exhibits a change in resistance value of more than 1.0 and not more than 6.2 when exposed to a reducing gas with a concentration of 5 ppm or an oxidizing gas with a concentration of 5 ppm.

12. A substrate, A pair of electrodes provided on the substrate; a structure film formed on the electrode, and / or a particle according to any one of claims 3 to 5; A gas sensor having The structure film includes a composite of a nickel-containing substance and a manganese-containing substance, and is configured by bonding a sheet-like structure having a sheet-like form and / or a sheet-like structure laminate having two or more laminated sheets of the sheet-like structures in a crystal-grown state, A gas sensor which exhibits a change in resistance greater than 1.0 and not greater than 1.8 with respect to acetone at a concentration of 200 ppb.

13. A substrate, A pair of electrodes provided on the substrate; a structure film formed on the electrode, and / or a particle according to any one of claims 3 to 5; A gas sensor having The structure film includes a composite of a nickel-containing substance and a manganese-containing substance, and is configured by bonding a sheet-like structure having a sheet-like form and / or a sheet-like structure laminate having two or more laminated sheets of the sheet-like structures in a crystal-grown state, A gas sensor characterized in that, when a resistance change in response to acetone is compared with a resistance change in response to isoprene, toluene, ammonia, hydrogen, or nitrogen dioxide, an acetone selectivity ratio of greater than 1.0 and less than or equal to 5.1 is obtained.

14. A substrate, A pair of electrodes provided on the substrate; a structure film formed on the electrode, and / or a particle according to any one of claims 3 to 5; A gas sensor having The structure film includes a composite of a nickel-containing substance and a manganese-containing substance, and is configured by bonding a sheet-like structure having a sheet-like form and / or a sheet-like structure laminate having two or more laminated sheets of the sheet-like structures in a crystal-grown state, A gas sensor capable of detecting one or more of acetone, isoprene, toluene, ammonia, hydrogen, and nitrogen dioxide gases at a concentration of 5 ppm.

15. A substrate, A pair of electrodes provided on the substrate; a structure film formed on the electrode, and / or a particle according to any one of claims 3 to 5; A gas sensor having The structure film includes a composite of a nickel-containing substance and a manganese-containing substance, and is configured by bonding a sheet-like structure having a sheet-like form and / or a sheet-like structure laminate having two or more laminated sheets of the sheet-like structures in a crystal-grown state, A gas sensor capable of detecting acetone gas at a concentration of 200 ppb.

Citation Information

Patent Citations

  • Preparation method for antimony-doped flower-ball-shaped tin dioxide gas-sensing material

    CN105152202A

  • LCMO-NiO nanocomposite film material and preparation method thereof

    CN105986227A

  • Magnetoresistance tunnel junction element

    JP2000012920A

  • SnO2-BASED GAS SENSOR

    JP2018031696A

  • Gas detection device

    JP2020041833A